Desafíos en la interfaz entre el conocimiento interdisciplinario, la gestión y las políticas públicas en la zona costera de Uruguay - Daniel Conde (INTER DISCIPLINA, 2026)
This study analyzes the tensions and opportunities at the interface between interdisciplinary knowledge, management, and public policy in Uruguay’s coastal zone. Through the examination of 14 local cases, critical factors affecting the effectiveness of coastal management processes are identified. The legal formalization of environmental decisions emerges as a key element to ensure continuity beyond political cycles, while genuine social participation strengthens the legitimacy and sustainability of interventions. The study highlights the importance of effective communication between science, society, and policy, which requires permanent spaces for interaction, prior knowledge among actors, and the translation of knowledge. Scaling up successful experiences faces structural, functional, and contextual barriers and is more feasible in limited areas and under favorable ecological and institutional conditions. It is pointed out that the high academic cost of interdisciplinary practices limits the development of public policies, and a review of incentives and institutional evaluation metrics is proposed. It is concluded that adaptive, collaborative, and multi-scale governance, based on stakeholder networks, learning cycles, and knowledge democratization, is essential for consolidating effective and far-reaching coastal public policies.